Baropodometric quantification and implications of muscle coactivation in the lower limbs caused by head movement: A prospective study. Issue 1 (January 2020) - Nisand, Michaël; Callens, Christian; Destieux, Christiane; Dyer, Joseph-Omer; Chanson, Jean-Baptiste; Sauleau, Erik; Mutter, Catherine
Abstract: Background: In healthy young adults, muscle coactivation can sometimes be induced by remote voluntary contractions when the motor task is forceful, maximal, tiring, or cyclic and brief. Objectives: To show that a change in plantar pressure is an unequivocal response to backward movement of the head, and to contribute to a better understanding of physiotherapy methods that involve remote muscle activation. Methods: Involuntary coactivation was quantified as a percentage of the anteroposterior plantar pressure distribution, using a baropodometric platform in a population of young adults. The baropodometric data were collected from a 1s recording after 30 s in the reference condition, and from 1s recordings during the first second and then during the 120th second in the test condition. The results were analyzed with Bayesian statistics (Markov chains and Monte Carlo integration techniques). Results: 90 adults participated in the study (age range: 19–26; 38 males and 52 females). The forefoot plantar pressure increased in all cases, by a mean multiplicative factor (on a logit scale) of 1.12 (from 72.24% to 74.45%) when the head was aligned over the trunk. Conclusions: This 90-participant trial confirmed our initial hypothesis: a increase in forefoot plantar pressure is a systematic response to the motor task (head movement), and suggests greater recruitment of the plantar flexor muscles. A spinal reflex and/or a previously unknown form of motor overflow might be involved in this phenomenon. These results support the development of inductive physiotherapy techniques based on remote muscle activation in the treatment of musculoskeletal disorders. Clinicalstrial.gov identifier: NCT02320097.